Educação, revolução e experiência: a Cruzada Nacional de Alfabetização e a Revolução Sandinista (1980) - Ázara, Túlio Almeida de (2020)
The theme of this dissertation is about the great literacy campaign in Nicaragua called the National Literacy Crusade undertaken by the sandinistas shortly after their seizure of power in the event that historically became known as the Sandinista Revolution in 1979. In this sense, the objective of this study is think of education as a revolutionary project in the specific case of this revolution. The bibliographic review points to Paulo Freire as the theoretical framework for this literacy campaign. Thus, we intend to reflect on how the education process took place in the aforementioned campaign, bearing in mind: 1) education as a political act, in the prepositions of the Brazilian thinker Paulo Freire - the political dimension of this campaign, aiming to identify the objectives of the project of National Literacy Crusade (1980) and consider some developments of this campaign for the Nicaraguan nation; 2) some founding concepts of Paulo Freire - the author's considerations about experience and education, which run through the concepts of knowledge of the experience made, dialogicity and humanist-liberating education. To this end, the sources of this research are official documents from the Sandinista government and the Nicaraguan Ministry of Education, periodicals of the main communication vehicles in Managua in the 1980s and interviews with literacy teachers who participated in the campaign. The results of this research indicate that: 1) the literacy campaign was for the brigadiers to continue the revolution, therefore, aligned with the revolutionary project and engaged with Sandinismo; 2) despite the short space of time, they achieved expressive results that corroborated the policy of the Sandinista National Liberation Front; 3) although Paulo Freire's system was not used exactly as it was thought in the Pedagogy of the Oppressed, there were indications of freirian orientations played both in the elaboration and in the concretization of the campaign by literacy brigades, such as the break with traditional education or “banking” and the existence of dialogues between the “literacy teacher” (from the urban culture) and the student belonging to the rural culture in an education engaged with the “ragged”.